Cooperative learning strategies to reinforce english as a foreign language reading comprehension skills in junior students - Dávila Eskola, Oscar Germán (2021)
To reinforce the English as a foreign language reading comprehension skills by applying a cooperative learning strategies guide in Junior students at Unidad Educativa Victor Manuel Peñaherrera. 2020-2021.